2015
DOI: 10.1017/s0001924000010472
|View full text |Cite
|
Sign up to set email alerts
|

Flight in nature I: Take-off in animal flyers

Abstract: In this review paper, several take-off techniques of different species of animal flyers and gliders, both extinct and extant, are analysed. The methods they use vary according to animal group and size. Smaller animals, such as insects, rely on the use of transient aerodynamic techniques or the use of stored elastic energy. Medium-size flyers such as birds, bats, and other mammal gliders initiate flight by a jump which involves leg and wing movement coordination. The largest animals to fly, the extinct pterosau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…5) and contributes to lowering down the entire body. Previous studies in a variety of birds (Earls 2000;Heppner and Anderson 1985;Tobalske et al 2004) suggested that a continuum exists in the take-off strategies, where tiny birds (3-5 g) show a crouching movement less exaggerated than the one displayed in small birds (15-90 g), which is itself less pronounced than in medium birds (100 g to 1.5 kg) who exhibit a motion similar to a squat (Manzanera and Smith 2015). Zebra finch and diamond dove fall at the two sides of the small bird category, with a less pronounced pitching movement in zebra finch compared to diamond dove.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5) and contributes to lowering down the entire body. Previous studies in a variety of birds (Earls 2000;Heppner and Anderson 1985;Tobalske et al 2004) suggested that a continuum exists in the take-off strategies, where tiny birds (3-5 g) show a crouching movement less exaggerated than the one displayed in small birds (15-90 g), which is itself less pronounced than in medium birds (100 g to 1.5 kg) who exhibit a motion similar to a squat (Manzanera and Smith 2015). Zebra finch and diamond dove fall at the two sides of the small bird category, with a less pronounced pitching movement in zebra finch compared to diamond dove.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, take-off involves significant transitional motions of the articulated system between two locomotor positions, combined with the production of enough acceleration to propel itself into the air. In small animals, such as insects or small birds, take-off generally starts with a jump (Alexander 1995;Dudley 2002;Manzanera and Smith 2015), consisting in a crouching movement followed by a rapid extension of the legs. It has been observed that the first wing downstroke starts after lift-off (Brackenbury 1992;Card and Dickinson 2008;Earls 2000;Manzanera and Smith 2015;Provini et al 2012b;Zumstein et al 2004), suggesting that the legs produce most of the acceleration needed to become airborne.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wingless or leg-assisted insects like fleas, locusts or hoppers use their powerful legs to jump rapidly into the air, which is usually featured with a short duration, high acceleration, emergence-involvement and uncontrollable trajectory [4,[8][9][10] . Meanwhile, the wing-assisted takeoff usually features volunteer takeoff, ground effect and controllable trajectory [11,12] .…”
Section: Introductionmentioning
confidence: 99%